Potret Kebijakan Inovasi Pelayanan Publik di Indonesia Tahun 2020 - Suranto Suranto; Awang Darumurti; Dwian Hartomi Akta Padma Eldo; Akhmad Habibullah (Universitas Teuku Umar, 2021)
Public service innovation is the primary key to good governance development launched in most countries in the world, including Indonesia. There have been many innovative programs carried out by several Ministries, Institutions, and Local Governments in practice. Still, there is no comprehensive portrait related to the tradition of public service innovation. The study aims to obtain a complete description of the public service innovation practices in 2020 using indicators of innovators, types of innovation, goals and achievements of innovation, policy sector and geographical aspects. This descriptive-explorative research type applies an archival method that focuses on secondary data usage, and the results are then analyzed using both Nvivo 12 and SPSS. The result shows that: (1) Innovators are dominated by local governments because the scope of service issues is more varied and specific. (2) The type of policy innovation that is oriented to the process aspect dominates the proposed proposal because of the ease and implementation factor. (3) Most innovation outcomes are in problem-solving, which shows the orientation to problem-solving that is more practical and real impact. (4) The health sector is getting more attention in policy innovation because of the trend of actual needs in the field, making it the primary sector. (5) The institution participants in Java island are much higher than outside Java, showing the imbalance in the quality of human resources